2016
DOI: 10.1016/j.schres.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use in the immediate 5-year premorbid period is associated with increased risk of onset of schizophrenia and related psychotic disorders

Abstract: Objectives Several studies suggest that adolescent marijuana use predicts earlier age at onset of schizophrenia, which is a crucial prognostic indicator. Yet, many investigations have not adequately established a clear temporal relationship between the use and onset. Methods We enrolled 247 first-episode psychosis patients from six psychiatric units and collected data on lifetime marijuana/alcohol/tobacco use, and ages at onset of prodrome and psychosis in 210 of these patients. Cox regression (survival anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 46 publications
4
55
0
Order By: Relevance
“…Altogether, these findings are consistent with a recent study evaluating the different patterns of change in cannabis use on subsequent psychosis onset (Kelley et al, 2016). The authors reported that (a) the steeper the growth in cannabis use in the few years before conversion to psychosis, the higher the risk of conversion, and (b) those with an early onset of cannabis use who follow a decreasing trajectory of use have a similar risk of psychosis onset to nonusers (Kelley et al, 2016). Therefore, it seems that both age of onset and cumulative use information are insufficient measures and are likely to underestimate the real-life impact of cannabis use on psychotic symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Altogether, these findings are consistent with a recent study evaluating the different patterns of change in cannabis use on subsequent psychosis onset (Kelley et al, 2016). The authors reported that (a) the steeper the growth in cannabis use in the few years before conversion to psychosis, the higher the risk of conversion, and (b) those with an early onset of cannabis use who follow a decreasing trajectory of use have a similar risk of psychosis onset to nonusers (Kelley et al, 2016). Therefore, it seems that both age of onset and cumulative use information are insufficient measures and are likely to underestimate the real-life impact of cannabis use on psychotic symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Adolescents were shown to be at 159% increased odds of being classified in the increasing PLE trajectory for every unit increment in the cannabis frequency scale (which ranges from no use, occasional use, once a month, once a week, couple times per week, to every day). Altogether, these findings are consistent with a recent study evaluating the different patterns of change in cannabis use on subsequent psychosis onset (Kelley et al., ). The authors reported that (a) the steeper the growth in cannabis use in the few years before conversion to psychosis, the higher the risk of conversion, and (b) those with an early onset of cannabis use who follow a decreasing trajectory of use have a similar risk of psychosis onset to nonusers (Kelley et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…As part of a larger project examining the effects of premorbid marijuana use on early-course psychosis (Kelley et al, 2015), 104 patients (recruited and assessed between August 2008 and March 2011) had available data on the key variables of interest in this analysis. Participants were recruited from the inpatient psychiatric units ( n =82) or psychiatric emergency service ( n =5) of a large, urban, university-affiliated, public sector hospital and from a suburban county psychiatric crisis center ( n =17), both in Atlanta, Georgia, and both of which serve a predominantly African American population.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with earlier examinations of the cannabis–psychosis relationship (Andreasson, Allebeck, Engstrom, & Rydberg, 1987; Arseneault, Cannon, Witton, & Murray, 2004; Arseneault et al., 2002; Compton et al., 2009; Di Forti et al., 2009, 2014; Kelley et al., 2016; McLaren, Silins, Hutchinson, Mattick, & Hall, 2010; Moore et al., 2007) (for a meta‐analysis, see Large, Sharma, Compton, Slade, & Nielssen, 2011). The effect of gender on AoP was significant in our study, with males being at risk of developing psychosis earlier than females.…”
Section: Discussionmentioning
confidence: 99%